Dry inoculum (active ingredient in Aflasafe): reduces manufacturing costs for Aflasafe and addresses barrier to commercialization - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
Three companies received the dry spores to manufacture Aflasafe products for use in their own countries and for countries where manufacturing facilities are yet to be started/finished, enabling the commercial production of crops in Senegal, The Gambia, Burkina Faso, Tanzania, Malawi, Mozambique, and Nigeria, to be treated with Aflasafe.